2007
DOI: 10.1016/j.molimm.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 inhibition of IFN-γ-induced signaling and Th1 gene expression in CD4+ T cells is Smad3 independent but MAP kinase dependent

Abstract: In addition to classic Smad signaling pathways, the pleiotropic immunoregulatory cytokine TGF-β1 can activate MAP kinases, but a role for TGF-β1-MAP kinase pathways in T cells has not been defined heretofore. We have shown previously that TGF-β1 inhibits Th1 development by inhibiting IFN-γ's induction of T-bet and other Th1 differentiation genes, and that TGF-β1 inhibits receptorproximal IFN-γ-Jak-Stat signaling responses. We now show that these effects of TGF-β1 are independent of the canonical TGF-β1 signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 29 publications
(43 reference statements)
2
32
0
Order By: Relevance
“…This heterotetrameric receptor complex is then able to suppress DC and helper T-cell function through regulation of the Smad complex and non-Smad MAP (mitogen-activated protein) kinases (12,18). Polak et al recently showed that tumor-infiltrating, tolerogenic DCs and suppressor T-cell lymphocytes in malignant melanoma correlate with immunosuppressive TGF-b1, TGF-b2, and IL-10 expression (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heterotetrameric receptor complex is then able to suppress DC and helper T-cell function through regulation of the Smad complex and non-Smad MAP (mitogen-activated protein) kinases (12,18). Polak et al recently showed that tumor-infiltrating, tolerogenic DCs and suppressor T-cell lymphocytes in malignant melanoma correlate with immunosuppressive TGF-b1, TGF-b2, and IL-10 expression (15).…”
Section: Discussionmentioning
confidence: 99%
“…9) which, rather than cross-priming CD8 þ cytotoxic T cells, inhibit T-effector antitumor activities (9)(10)(11) in part through TGFb-dependent suppression of antigen-presenting dendritic cell (DC) processes (12). Further, both tumor-infiltrating, tolerogenic DCs and suppressor T lymphocytes express the TGF-b receptor 1 (TGF-bR1) and are therefore susceptible to immunosuppressive modulations by TGF-b1 and TGFb2 produced by tumor cells (13)(14)(15)(16)(17)(18). Circulating Th1-suppressive cytokines, including TGF-b and IL-10, that are frequently elevated in patients with advanced cancer mediate immune suppression in tumor-bearing animal models by downregulating antigen recognition, Th1 activation, and antitumor immune effector functions (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…This alteration correlated with impaired SMAD3 activation and could explain the emergence of aberrant IFNg þ cells among Coro1a À/À Th17 CD4 þ T cells. Accordingly, Takimoto et al reported that the TGFb-mediated suppression of IFNg was partially impaired in both Smad2 À/À T cells and in Smad3 À/À T cells, and fully abrogated in the double knockout T cells [52,53]. Furthermore, it has been shown that Th17 cell population is heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising in that TGF-β has been shown to restrict Th1 cells' TBET and IFN-γ secretion in other contexts (54,55). However, these molecules seem sufficiently suppressed during chronic infection, even in the absence of TGF-β signaling.…”
Section: Cd49dmentioning
confidence: 99%